PENGARUH KUALITAS PRODUK, DESAIN PRODUK, DIRECT MARKETING DAN STRATEGI DIFERENSIASITERHADAP KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI MOTORS - Reni Anggraini; Christina Dewi Wulandari; Sriyanto Sriyanto; Fema Dewita (Universitas Veteran Bangun Nusantara, 2023)
Mitsubishi Motors presents Monochoque SUVs such as the Pajero Sport, LMPV (Low Multi Purpose Vehicle) such as Xpander and LSUV (Low Sport Utility Vehicle) such as Eclipse and Outlander. The purpose of this study was to analyze Product Quality (X1), Product Design (X2), Direct Marketing (X3) and Differentiation Strategy (X4) on Purchasing Decisions (Y) and to find out which variables are most dominant in Mitsubishi Motors car buying decisions. The analytical method in this study used primary data which was processed using SPSS version 26. The analysis technique used was validity and reliability testing, the classic assumption test consisting of heteroscedasticity test, multicollinearity test, normality test, multiple linear regression analysis, t test, test f and test the coefficient of determination (R2). Valid data collected by 100 respondents. The sample method in this study was non-probability sampling with purposive sampling technique.The results showed that partially Product Quality, Product Design, Direct Marketing had an effect on Purchasing Decisions, while the Differentiation Strategy had no effect on Purchase Decisions. Product Quality, Product Design, Direct Marketing and Differentiation Strategy simultaneously influence Purchase Decision.